Penerapan Metode SDLC Pada Pembangunan Sistem Informasi Akuntansi UMKM Toko Khasanah - Abdul Hafiz Tanjung; Dian Nurul Khazaainatu Qurrota A’yun (JURNAL BISNIS dan TEKNOLOGI, 2024)
Toko Khasanah is one of the micro, small and medium enterprises (MSMEs) selling daily necessities. The recording and processing of transaction data are not in accordance with the accounting cycle or still done manually on paper books. With a desktop-based accounting information system that can help computerized transaction data management, it can reduce the risk of recording errors or loss of transaction evidence. Each transaction is recorded in a journal which will later be posted to the general ledger for financial statement preparation such as balance sheet, income statement, changes in equity statement, cash flow statement or other reports such as sales/purchase report, inventory card and accounts payable automatically. The method used to develop this system is SDLC (System Development Life Cycle) with planning analysis design implementation testing phases. Java programming language was used to write code using Netbeans IDE while data storage uses Mysql. The results show needs for an accounting information system for cash sales transactions; credit purchases; debt records; inventory management; and financial report generation.